Reconstruction Of Dispute Resolution Mechanism Through Arbitration In Civil Procedure Law - Abuthalib, Cut Nangrie Sari (Universitas Pahlawan Tuanku Tambusai, 2024)
This paper analyses and reconstructs Indonesia's civil procedural law arbitration dispute settlement process to increase efficacy and efficiency, notably in executing rulings and reducing court involvement. Although arbitration is a final and binding dispute settlement procedure, its implementation is nevertheless difficult. The reliance on district courts to execute arbitration rulings frequently leads to unwarranted judicial involvement, lowers efficiency, and causes legal confusion. High fees and restricted accessibility for small and medium firms are other arbitration challenges in Indonesia. Statutory laws, legal theories, and general principles in civil procedural law guiding arbitration are analysed using a normative legal research technique. This research relies on primary sources like Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution and secondary sources like scientific publications and legal literature. The research found that court participation in arbitration decision implementation is limited, indicating the necessity to restructure the arbitration procedure. Increased use of local arbitration institutions like the Indonesian National Arbitration Board and technology in arbitration proceedings may lower costs and speed up conflict settlement. Technology, such online arbitration platforms, may make arbitration more accessible and efficient, particularly for small and large businesses. Thus, Indonesia requires a thorough arbitration reform to make conflict resolution more sensitive to economic realities and societal requirements.